Gestión empresarial y su relación con el desarrollo sostenible de las pequeñas unidades agrícolas del sector cuatro mangas del cantón Quevedo, año 2015 - Porro Reinoso, Juliana Lilibeth (2015)
This study for the Management and its relationship to sustainable development of small agricultural units in the sector Four Sleeves Canton Quevedo seeks to promote community development through based on technical assistance, preferential loans and due advice from mechanisms government agencies, rural issues identified in Ecuador. Much of the rural population depends directly on agriculture, but there is lack of training and modernization, so there is low production indicators compared to other regions, there is an inadequate management of the environment, or which creates problems of desertification, deforestation, depletion of water sources and disappearance of species among others; there is lack of market information for marketing, little information for making long-term decisions. This research project will help to farmers in the sector undertake a market study that will achieve better marketing of their products, in addition to establishing economic development strategies such as reforestation programs, promote the process of modernization, strengthening assistance technique that will allow smallholders sector apply a business management system that will help them improve the quality of life through a new venture related to the improvement in the marketing of their products.